Phenolic Profile, Fatty Acid and Essential Oil Composition Analysis and Antioxidant, Antialzheimer and Antibacterial Activities of Verbascum flavidum Extracts - Mehmet Boğa (Science Faculty of Chiang Mai University, 2019)
This paper is the first report about phytochemical analysis with LC-MS/MS and biological activities of Verbascum flavidum (Boiss.) Freyn & Bornm. Rutin (1077.09±77.47 µg analyte/g extract) and chlorogenic acid (1012.42±97.18 µg analyte/g extract) were determined the most abundant phenolics in V. flavidum. The main components of fatty acid were found to be palmitic (30.3%) and oleic acids (17.9%); while the major essential oils were determined as arachidic acid (16.4%) and α-selinene (8.9%) by GC-MS analysis. In DPPH free radical scavenging activity the methanol extract showed higher activity than BHT with 72.62% inhibition at 100 µg/mL concentration. The methanol and water extracts of V. flavidum showed 86.01 % and 87.39 % inhibition in ABTS cation radical scavenging assay at 100 μg/mL concentration, respectively. The methanol extract showed moderate activity against E. coli with 250±0.3 MIC value and with 15 mm inhibition zone diameter at 30 mg/mL concentration.